Creative Learning Collaboration: Enhancing Cognitive Literacy In Early Childhood Learners - Sa'idah Ahmad; Alif Mudiono; Ahmad Samawi (Institut Agama Islam An-Nawawi Purworejo, 2025)
This study aims to analyse creative learning collaboration in improving cognitive literacy in early childhood students. The study uses a qualitative approach of case study type, where researchers try to reveal the meaning of creative learning in improving children's cognitive literacy. Data were collected through interviews, observations and documentation. Data analysis was done through data display, reduction, and conclusion drawing. The study results indicate that the increase in cognitive literacy in early childhood occurs due to the collaboration of teachers and children in project-based learning, the active role of parents in supporting learning at home, the use of creative media and teaching aids together, and interdisciplinary and contextual learning. This study provides implications about early childhood cognitive literacy, requiring a collaborative, contextual, and innovative learning approach and active support from parents. Other PAUD institutions can adopt this model as an effective strategy to holistically develop children's thinking skills from an early age.